SMART HOME SYSTEM BASED ON THE INTERNET OF THINGS USING NODEMCU AND ANDROID APPLICATIONS - Muhammad Syahputra Novelan; Aminuddin Indra Permana (INFOKUM, 2022)
Smart home systems aim to maximize surveillance, monitoring, security and so on. The way this system works is that it integrates telecommunications and system controllers from a chip or NodeMCU, so it is called the Internet of Things. In this study, create or design a smart home that aims to make it easier to control existing equipment at home remotely and when traveling out of town with the Internet Of Things system. Besides, it's not just controlling remotely but by monitoring it by using an Android smartphone. The devices used in the Smart Home system design are divided into several parts, namely input, process and output. Part of the input consists of a room temperature sensor, part of the process consists of a Microcontroller or uses a NodeMCU, and part of the output is an LED as an indicator and sound or using a Buzzer module. The results of the tests carried out by the system designed that the smart home runs well overall starting from the android application and receiving data from the microcontroller and sending notifications to the sensor readings